(untitled) (Research, Society and Development, 2021)
This study aimed to analyze the impact of the COVID-19 pandemic on the care of people with Sexually Transmitted Infections (STIs) in a region of low human development, located in Minas Gerais, Brazil. Methods: The number of monthly procedures during pandemic period, January to December 2020, and comparison period, January to December 2019, in a SUS regional clinic, a reference for STIs, were analyzed. Visits were categorized into follow-up appointments, rapid tests, viral loads and first appointment due a recent diagnosis. Comparison between both periods was performed by frequency analysis, difference in the mean monthly attendances (DM) and prevalence ratios (PR), considering ratio between the proportion of attendances in the pandemic period/proportion of attendances in the comparative period. During the pandemic period, the average number of monthly consultations reduced for all consultations (DM = -105.25) and categories. Proportion of consultations reduced for rapid tests (PR = 0.46; 95% CI = 0.41-0.52) and first consultation due recent diagnosis (PR = 0.90; 95% CI = 0.65-1, 25), procedures that are usually scheduled by the user. There was an increase in the proportion of follow-up visits (PR = 1.18; 95% CI = 1.09-1.27) and viral load tests (PR = 1.41; 95% CI = 1.32-1, 88), monitoring procedures usually scheduled by the clinic. There was a trend to maintain risk exposure for STIs. Conclusion: These findings may guide better strategies to care for individuals with STIs.